Evaluation of the Diagnostic Efficacy of Intra Oral Digital Radiography With and Without Zoom Option Software in the Detection of Occlusal Dentinal Caries: An in Vitro Study - Sandra Mehr-Alizadeh; Donya Sadri; Saeid Nemati; Soodeh Sarikhani; Arash Zafarfazeli (Islamic Dental Association of Iran, 2012)
Background and Aim : The purpose of this study was to evaluate the diagnostic precision of zoom option of Cygnus Ritter CCD intraoral digital sensor compared to original digital radiography in the detection of occlusal dentinal caries .  Materials and Methods : Eighty-six extracted premolars with no apparent clinical caries were selected. Two methods were used for radiography namely, digital radiography using a Cygnus Ritter CCD sensor and then zoom option was applied to the original radiographs. Four maxillofacial radiologists observed the original digital and the same radiographs with zoom option to detect occlusal dentinal caries subsequently recording it in a five-grade scale.  Microscopic sections evaluated by a pathologist were used as the gold standard for caries detection. The data were analyzed with a proportion test and processed with SPSS maxillofacial 14 soft ware .  Results : Statistical analysis showed a sensitivity of 52.2% (71) (CI: 95 % ) for zoom option in the detection of occlusal dentinal caries (P<0.05). The specificity was shown as 68.8% (143) (P>0.05). The ppv was calculated as 52.2% (179) (P<0/.05) and npv as 68.8% (236) (P<0.05) and the accuracy was 62.2% (214) (P<0.05).  Conclusion : The zoom option of Cygnus Ritter CCD sensor showed a significantly higher diagnostic sensitivity, ppv, npv and accuracy compared to original digital radiographs, but the zoom option of that sensor did not show a significantly higher diagnostic specificity compared to original digital radiographs .  Key words: Dentinal caries - Digital radiography - Digital enhancement - Image processing - Zoom